KIR2DS2+ NK cells in cancer patients demonstrate high activation in response to tumour-targeting antibodies - Graham, Lara V.; Fisher, Jack G.; Doyle, Amber D. P.; Sale, Ben; Del Rio, Luis; French, Albert J. E.; Mayor, Neema P.; Turner, Thomas R.; Marsh, Steven G. E.; Cragg, Mark S.; Forconi, Francesco; Khakoo, Salim I.; et al. (Frontiers in Oncology, 2024)
Strategies to mobilise natural killer (NK) cells against cancer include tumour-targeting antibodies, NK cell engagers (NKCEs) and the adoptive transfer of ex vivo expanded healthy donor-derived NK cells. Genetic and functional studies have revealed that expression of the activating killer immunoglobulin-like receptor KIR2DS2 is associated with enhanced function in NK cells from healthy donors and improved outcome in several different malignancies. The optimal strategy to leverage KIR2DS2+ NK cells therapeutically is however currently unclear. In this study, we therefore evaluated the response of KIR2DS2-expressing NK cells to activation against cancer with clinically relevant tumour-targeting antibodies and following ex vivo expansion. We identified that KIR2DS2high NK cells from patients with chronic lymphocytic leukaemia and hepatocellular carcinoma had enhanced activation in response to tumour-targeting antibodies compared to KIR2DS2- NK cells. However, the superior function of healthy donor derived KIR2DS2high NK cells was lost following ex vivo expansion which is required for adoptive transfer-based therapeutic strategies. These data provide evidence that targeting KIR2DS2 directly in cancer patients may allow for the utilisation of their enhanced effector function, however such activity may be lost following their ex vivo expansion.